Possibilities to implement pinch analysis in the steel industry : a case study at SSAB EMEA in Luleå - Grip, Carl-Erik; Harvey, Simon; Isaksson, Johan; Karlsson, Jonny (Luleå tekniska universitet, Energivetenskap, 2011)
Steelmaking is an energy intensive industry. Much development work has been accomplished during the past years to make the processes more efficient. Process integration has come to play an important role for identifying efficiency measures, using mathematical programming as general tool. So far only a few minor process integration studies using pinch analysis have been made in this type of industry, and only on smaller subsystems.This paper presents the results of a pinch targeting study that was conducted at the Swedish steel making company SSAB EMEA in Luleå. The pinch analysis methodology was originally developed to study heating, cooling and heat exchange in process systems with many streams. In the steel industry there arerelatively few streams that are appropriate for heat exchange. This limits the use of pinch analysis. However, this study demonstrates that pinch analysis is a powerful tool for certain subsystems, especially the gas cleaning unitof the coke plant. The paper includes several suggestions for improved energy efficiency in this section of the steel plant. Godkänd; 2011; 20111003 (cargri)